ABP791: Applied Business Project I / Arshad Ayub Graduate Business School - UiTM, Arshad Ayub Graduate Business School (2019)
This course is a platform in understanding the role of business research in shaping decisions. This specialized course covers topics such as the nature of research business problems, research design, theoretical frameworks, scales and measurement, questionnaire design technique and procedures. Additionally, data processing, analyses and interpretations will be discussed. A structure of research proposal and presentation of research report will be the ultimate outcome.